Does organophosphorus poisoning increase the risk of staphylococcal ventilator associated pneumonia? – a retrospective study - Avijit Chauhan; Hariswar Pari; Radha Sugumaran; Venkateswaran Ramanathan (Journal of Infection in Developing Countries)
Introduction: The aim of this study was to determine the clinical predictors of staphylococcal ventilator-associated pneumonia (VAP) and to compare the outcomes of staphylococcal VAP with non-staphylococcal VAP.